(untitled) (International Journal of Irrigation and Water Management, 2022)
Response surface methodology (RSM) is defined as a collection of mathematical and statistical methods that are used to optimize a product or a process. In order to determinate optimum levels of nitrogen (N), water volume and plant density of onion (Allium cepa L.), and field experiment was carried out according to a central composite design as RSM in Azarshahr County, East Azerbaijan Province, Iran –repeated over two years (2011 and 2012). The treatments were designed based on low and high levels of N, irrigation and plant density as independent variables. Furthermore, bulb yield, N losses, N uses efficiency (NUE) and water use efficiency (WUE) were measured as response variables in a full quadratic polynomial model. Optimum rates of N, irrigation and plant density was suggested to achieve the target range of response variables based on three scenarios: Economic, environmental and eco environmental. The results showed that increasing of N fertilizer up to 160 kg N ha-1 led to increase in bulb yield. The amounts of 93.48 kg N ha-1 , 8930 m3 water ha-1 and 42.67 onions m-2 was found to be the optimum conditions for eco-environmental scenario. In general, it seems that resource use based on eco-environmental scenario may be the most favorable cropping strategy in onion production.